Liver dysfunction related to hepatitis B and C in patients with inflammatory bowel disease treated with immunosuppressive therapy. Issue 10 (24th June 2010) - Loras, C; Gisbert, J P; Mínguez, M; Merino, O; Bujanda, L; Saro, C; Domenech, E; Barrio, J; Andreu, M; Ordás, I; Vida, L; Bastida, G; et al.
Abstract : Background: There is no information about the frequency of liver dysfunction in patients with inflammatory bowel disease (IBD) treated with immunosuppressants and infected with hepatitis B (HBV) and/or C virus (HCV). Aim: To assess the influence of immunosuppressants on the course of HBV and HCV infection in IBD. Methods: Patients with IBD with HBV and/or HCV infection from 19 Spanish hospitals were included. Clinical records were reviewed for the type of immunosuppressant used, treatment duration, liver function tests and viral markers before, during and after each immunosuppressant. Logistic and Cox regression analysis were used to identify predictors of outcome. Results: 162 patients were included; 104 had HBV markers (25 HBsAg positive) and 74 had HCV markers (51 HCV-RNA positive), and 16 patients had markers of both infections. Liver dysfunction was observed in 9 of 25 HBsAg positive patients (36%), 6 of whom developed hepatic failure. Liver dysfunction in HCV was observed in 8 of 51 HCV-RNA positive patients (15.7%), and only one developed hepatic failure. The frequency and severity of liver dysfunction was significantly higher in HBV-infected patients than in HCV-infected patients (p=0.045 and p=0.049, respectively). Treatment with ≥2 immunosuppressants was an independent predictor of HBV reactivation (OR 8.75; 95% CI 1.16 to 65.66). The majority of patients without reactivation received only one immunosuppressant for a short period and/or prophylactic antiviral treatment. No definite HBV reactivations were found in anti-HBc positive patients lacking HBsAg. Conclusion: Liver dysfunction in patients with IBD treated with immunosuppressants is more frequent and severe in those with HBV than in HCV carriers and is associated with combined immunosuppression.